Data Resource: the Kent Integrated Dataset (KID) - Lewer, Dan; Bourne, Tom; George, Abraham; Abi-Aad, Gerrard; Taylor, Clint; George, Julie (International Journal of Population Data Science, 2018)
Introduction Electronic healthcare records from the UK are accessible to researchers via a number of platforms, but these platforms typically include data from a limited subset of health and care services. The Kent Integrated Dataset (KID) aims to provide insight into system-wide health and care utilisation for the whole population of Kent and Medway. Methods The KID uses pseudonymisation-at-source to link patient-level records from services including general practices, hospitals, community health services and social care. The design and governance of the dataset is led by local authorities, health commissioners and service providers. Results A population-level dataset has been developed, including data from April 2014 onwards. Data providers add new data on a monthly basis. The KID has been used to understand the costs associated with frailty, estimate the prevalence of rare conditions and compare the risk of non-elective hospitalisation between general practices. Conclusion The KID is a unique and rich dataset available to researchers who are investigating a broad range of public health questions. It provides system-level insight into patient journeys and care utilisation and supports commissioning based on patient needs.